Limiting prices or transferring money? An ex-ante assessment of alternative measures to cope with the hike in energy prices - Antonio F. Amores; Michael Christl; Paola De Agostini; Silvia De Poli; Sofia Maier (European Commission, Joint Research Centre (JRC), 2023)
The hike in energy prices across Europe in 2022 and 2023 led to significant government interventions. Several governments introduced 'energy price cap' measures to alleviate the increased burden on households' expenditures. This paper presents an ex ante assessment of the expected distributional impact of the inflation surge and the cushioning effect of these price cap policies introduced in 2023 in Germany, the Netherlands and Austria. Our analysis combines macroforecasting techniques with microsimulation methods and shows that the inflationary shock of 2023 will more severely affect those households at the bottom of the income distribution. Our results also highlight that the price cap measures will only partly absorb the negative distributional consequences of the inflationary shock while it would completely offset the increase in energy poverty. Additionally, we show that simpler measures, such as lump-sum cash transfers, are more efficient (considering government's budgetary costs) in cushioning the inequality-increasing effects of inflation, especially when such measures are targeted. Price caps, on the other hand, are more efficient in reducing energy poverty, given the non-negligible incidence of energy poverty in middle-income groups.
Keywords: H31; C81; Q48; 330; Energy; price cap; microsimulation; inequality; Europe